Analisis Kedudukan dan Peran Otoritas Jasa Keuangan (OJK) dalam Pengawasan dan Regulasi Sistem Perbankan Syariah di Indonesia - Khairul Hanif; Muhammad Albahi; Rozi Andrini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the position and role of the Financial Services Authority (OJK) in supervising and regulating the Indonesian Islamic banking system. This research uses a descriptive qualitative approach with library research methods. The study examines laws, OJK regulations, and scientific literature on Islamic financial supervision. This analysis highlights the OJK's dual function as a regulator and supervisor in maintaining sharia compliance, financial stability, and governance in Islamic banks. The findings reveal that the OJK holds a strategic position as an independent authority based on Law No. 21 of 2011 and Law No. 4 of 2023 concerning the Development and Strengthening of the Financial Sector. OJK's on-site and off-site supervision ensures transparency, risk management, and compliance with sharia principles. Challenges include limited human resources with dual expertise, weak harmonization with the National Sharia Council (DSN-MUI), and low public literacy. This study concludes that strengthening the role of the OJK requires increased institutional coordination, capacity building, and integration of maqasid al-shari’ah principles to ensure sustainable development of Islamic finance.